Expectations for a Future Job and Scientific Vocations on Secondary Education Students - Ángel Vázquez Alonso; María Antonia Manassero Mas (Universidad Autónoma de Baja California, 2009)
This study features a diagnosis on the expectations and priorities of secondary education students relative to their working future in the Balearic Islands (Spain), by means of a questionnaire which appraises the importance of several features of a job. Features like helping others (of major importance for girls) and creativity (of major importance for boys) are the most appraised by young people, while craftsmanship (radically rejected by girls) and environmental aspects are considered of less importance. According to the questionnaire's factors structure, the self-updating related aspects have major importance, while the manual dimension is the least important. Debate of these results appeals directly to school science, while as long as the improvement and attention of job expectations defy education and science teaching in school, mainly for the development of science vocations.